TELAAH KONSEPTUAL: DEEP LEARNING SEBAGAI PARADIGMA PEMBELAJARAN GENERASI ALPHA DAN BETA DALAM PENDIDIKAN ISLAM - Wiandani, Muhammad Alfan; Rosada, Rosiana Mahari; Wahyudi, Wahyudi; Khuriyah, Khuriyah (STRATEGY : Jurnal Inovasi Strategi dan Model Pembelajaran, 2025)
This article examines the need for a new learning paradigm for Generation Alpha and Generation Beta, who grow up in a rapidly evolving digital environment that significantly shapes their thinking patterns, learning behaviors, and educational challenges in Indonesia particularly the persistent low performance in literacy and numeracy as reflected in PISA results. The purpose of this study is to conceptually explore how deep learning integrated with the principles of mindful, meaningful, and joyful learning within Indonesia’s education policy can serve as a relevant pedagogical approach for digital-native generations, while also identifying its points of convergence and implications for Islamic education. Using a literature review method, this study analyzes current research on generational characteristics, deep learning theory, the Merdeka Curriculum framework, and classical Islamic scholarly traditions on the ethics of seeking knowledge. The findings reveal that Generation Alpha tends to exhibit shorter attention spans and higher digital dependency, while Generation Beta emerges as AI natives who require more contextual and reflective learning experiences. Deep learning offers a framework that strengthens metacognition, mental presence, meaning-making, and engaging learning experiences. Furthermore, the principles of mindful, meaningful, and joyful learning show strong alignment with the Islamic concepts of tahd?d al-qashd, ?u??r al-qalb, riy??at al-nafs, and mu??sabah within classical Islamic pedagogy. This article concludes that deep learning has the potential to enhance the quality of learning for digital generations while simultaneously reinforcing Islamic spirituality and character formation when implemented integratively, contextually, and with a transformative learner-centered orientation. ABSTRAK Artikel ini membahas kebutuhan paradigma pembelajaran baru bagi Generasi Alpha dan Beta yang hidup dalam lingkungan digital sangat cepat, yang berdampak pada pola pikir, cara belajar, serta tantangan pendidikan di Indonesia, terutama rendahnya capaian literasi dan numerasi yang ditunjukkan oleh hasil PISA. Tujuan penelitian ini adalah menelaah secara konseptual bagaimana deep learning yang dalam kebijakan pendidikan Indonesia dipadukan dengan prinsip mindful, meaningful, dan joyful learning dapat menjadi pendekatan pedagogis yang relevan bagi generasi digital, sekaligus melihat titik temu dan implikasinya terhadap pendidikan Islam. Penelitian ini menggunakan metode studi pustaka dengan menelaah literatur mutakhir tentang karakteristik generasi, teori pembelajaran mendalam, kebijakan Kurikulum Merdeka, serta khazanah adab penuntut ilmu dalam tradisi Islam klasik. Hasil kajian menunjukkan bahwa Generasi Alpha cenderung memiliki rentang atensi pendek dan ketergantungan digital tinggi, sementara Generasi Beta berkembang sebagai AI natives yang membutuhkan pembelajaran lebih kontekstual dan reflektif; deep learning menawarkan kerangka yang memperkuat metakognisi, kehadiran mental, keterhubungan makna, dan pengalaman belajar yang menggembirakan. Selain itu, prinsip-prinsip mindful, meaningful, dan joyful learning memiliki kesesuaian kuat dengan konsep tahd?d al-qashd, ?u??r al-qalb, riy??at al-nafs, dan mu??sabah dalam tradisi pendidikan Islam. Artikel ini menyimpulkan bahwa deep learning berpotensi meningkatkan kualitas pembelajaran generasi digital sekaligus memperkuat spiritualitas dan karakter Islami apabila diterapkan secara integratif, kontekstual, dan berorientasi pada transformasi peserta didik.